Dengue Fever Presenting with Severe Myositis-A Case Report: Life Sciences -General Medicine - Sainadh, Nandhyala Durga Venkata; P, Manimekalai.; Mc, Vinatha; Pon Divya Bharathi, Pujari Lokchaitanya (International Journal of Life Science and Pharma Research, 2023)
Dengue fever is one of the most common vector-borne diseases, which is a viral infection transmitted by female Aedes aegypti mosquitoes. It is most common in tropical countries like India. Dengue fever symptoms can range from a mild infection to severe flu-like sickness. Myalgia is a symptom of dengue infection. Dengue fever with myositis and/or high serum creatine phosphokinase (CPK) levels, on the other hand, is extremely uncommon. Dengue virus can cause myositis in many mechanisms. One of the most common mechanisms is by direct invasion of the myocytes by the dengue viruses. Myotoxins, Inflammatory cytokines have also been a part of the development of myositis. The clinical spectrum is broad, from the mild asymmetrical weakness of lower extremities to sudden progressive severe limb and trunk weakness, and even lung failure. This case study aims to show the rare neuromuscular complications of dengue fever, which can be managed well with a high index of suspicion. Our patient presented with fever and severe myalgia and was diagnosed with dengue. We started treating the patient with a provisional diagnosis of dengue-associated myositis. Significantly elevated CPK levels confirmed the myositis. Hereby, we are presenting a case of dengue fever with myositis with muscle weakness & elevated creatine phosphokinase (CPK) levels who recovered completely with early suspicion of dengue-associated myositis and early management. Hence, Physicians should have a high index of suspicion and early management of dengue-associated neuromuscular complications.